2004
DOI: 10.1111/j.1538-7836.2004.00723.x
|View full text |Cite
|
Sign up to set email alerts
|

A common ancestral mutation (C128X) occurring in 11 non‐Jewish families from the UK with factor XI deficiency

Abstract: mutation (C128X) occurring in 11 non-Jewish families from the UK with factor XI deficiency. J Thromb Haemost 2004; 2: 918-24. Summary. Factor XI (FXI) deficiency is a mild bleeding disorder that is particularly common in Ashkenazi Jews, but has been reported in all populations. In Jews, two FXI gene (F11) mutations (a stop codon in exon 5, E117X, type II, and a point mutation in exon 9, F283L, type III) are particularly common, but in other populations a variety of different mutations have been described. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
68
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(71 citation statements)
references
References 23 publications
3
68
0
Order By: Relevance
“…Our results confirm that the molecular basis of this disorder is largely heterogeneous outside the Jewish population [11][12][13]26].…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Our results confirm that the molecular basis of this disorder is largely heterogeneous outside the Jewish population [11][12][13]26].…”
Section: Discussionsupporting
confidence: 78%
“…Although the Type II mutation is also frequent among Iraqi Jews and Palestinian Arabs [9], Phe283Leu is almost unique in Ashkenazi Jews, but it can be rarely observed in other populations [10]. More than 150 FXI gene mutations have been so far reported (see http://www.med.unc.edu/isth/mutationsdatabases/FactorXI_2007.htlm, http://www.wienkav.at/kav/kar/ texte_anzeigen.asp?ID57137, and http://www.factorxi.com), and a founder effect has been demonstrated in a few populations in whom prevalent ancestral mutations were found (Cys38Arg in French Basques, Gln88X in French patients from Nantes, and Cys128X in English patients) [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…18 Haplotype analyses confirmed that the frequency of these mutations is due to founder effects. In particular, the C128X mutation is found in 2% of individuals screened for hemochromatosis in the UK, 18 and in 2% of normal individuals from the north-west of England, suggesting that severe FXI deficiency in the UK may be more common than previously thought. 19 The frequency of the C128X mutation is similar to that of the C38R mutation, which is present in 1% of French Basques.…”
Section: Introductionmentioning
confidence: 66%
“…4 Two less common mutations were described in Jews: type I, a splice-site mutation and type IV, a 14bp deletion between exon 14 and intron N. 5,6 Other relatively frequent mutations, C38R and C128X, were reported in French Basques and Britons, respectively. [7][8][9] More than 120 other sporadic mutations have been identified in different populations [http://www.med.unc.edu/isth, http://www.factorXI.org]. 10 Characterization of the growing number of FXI mutations has shed light on the relationship between structure and function of this protein, and has contributed to defining the importance of its various domains.…”
mentioning
confidence: 99%